Rejection of the name Borreliella and all proposed species comb. nov. placed therein - Margos, Gabriele; Castillo-Ramirez, Santiago; Cutler, Sally; Dessau, Ram B; Eikeland, Randi; Estrada-Peña, Agustin; Gofton, Alexander; Graña-Miraglia, Lucía; Hunfeld, Klaus-Peter; Krause, Andreas; Lienhard, Reto; Lindgren, Per-Eric; et al. (International journal of systematic and evolutionary microbiology, 2020)
Rejection (nomen rejiciendum) of the name Borreliella and all new combinations therein is being requested on grounds of risk to human health and patient safety (Principle 1, subprinciple 2 and Rule 56a) and violation to aim for stability of names, to avoid useless creation of names (Principle 1, subprinciple 1 and 3) and that names should not be changed without sufficient reason (Principle 9 of the International Code of Nomenclature of Prokaryotes).
Keywords: terminologie jako téma; Terminology as Topic; nomenclature; Lyme disease; Spirochaetales; Borrelia; Phylogeny; fylogeneze